Reformulasi Keyakinan Guru dalam Implementasi Kurikulum - Al Musanna (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2016)
This paper aims to provide another alternative perspective on teachers’ beliefs towards curriculum implementation. This study focuses on the essence of teacher’s belief in the curriculum implementation. It also gives attention to the reformulation approach of teacher belief. Based on literatur review, it reveals that the curriculum needs not only competent teachers but also positive beliefs teacher about the curriculum. Attention to the reformulation of teacher beliefs still in a peripheral and subordinate in praxis of curriculum development. Policy makers still in mainstreaming to develop teacher capability related to technical competence and procedural instruction. In fact, a number of researchers dictate that teacher beliefs significantly contribute to the success of the curriculum implementation. This literatur review concluded that teachers beliefs about the curriculum, academic climates, and interaction with learners are detrimental to the curriculum implementation. New beliefs and conceptions are at the heart of implementation. Reformulation of teacher beliefs requires a personalized approach to change and direct it positively to contribute to curriculum implementation. ABSTRAKGuru dan kurikulum merupakan unsur substansial dalam praksis pendidikan. Kurikulum yang terdiri atas serangkaian rencana terkait tujuan, materi dan strategi pengembangan iklim pembelajaran dan indikator penilaian memerlukan guru yang tidak hanya kompeten, tetapi juga memiliki keyakinan yang positif terhadap kurikulum. Perhatian pada reformulasi keyakinan guru masih berada pada posisi periferal dan tersubordinasi oleh pengarus-utamaan (mainstreaming) pengembangan kemampuan guru terkait kompetensi teknis dan prosedural pengajaran. Padahal, dimensi keyakinan guru berkontribusi penting pada keberhasilan dan kebermaknaan kurikulum. Keyakinan guru terhadap kurikulum yang dijewantahkan melalui interaksi dengan peserta didik merupakan determinan implementasi kurikulum. Keyakinan guru memerlukan pendekatan personal untuk mengubah dan mengarahkannya sehingga berkontribusi positif dalam implementasi kurikulum.